Treatment effects of dapagliflozin in patients with aortic stenosis undergoing transcatheter aortic valve implantation across left ventricular ejection fraction - Sergio Raposeiras Roubín; Rafael Gonzalez-Manzanares; Ignacio Amat-Santos; María Melendo Viu; David Dobarro; Diego López Otero; Luis Nombela Franco; Livia Gheorge; Jorge Sanz-Sánchez; Baladrón Zorita Carlos; Soledad Ojeda; Andrés Iñiguez Romo; et al. (European Journal of Heart Failure, 2026)
Abstract Aims Sodium–glucose cotransporter 2 (SGLT2) inhibitors improve outcomes in heart failure (HF) across the left ventricular ejection fraction (LVEF) spectrum, but patients with severe valvular heart disease have been excluded from pivotal trials. We investigated the efficacy and safety of dapagliflozin across the full range of baseline LVEF in elderly patients undergoing transcatheter aortic valve implantation (TAVI). Methods and results DapaTAVI was a pragmatic, multicentre, randomized, open-label trial with blinded endpoint adjudication conducted at 39 Spanish centres. Patients with severe aortic stenosis undergoing TAVI were randomized after the procedure to dapagliflozin 10 mg once daily or standard of care. The primary endpoint was a composite of all-cause death or worsening HF. Among 1223 patients with available baseline LVEF, 213 (17.4%) had LVEF ≤40% and 1010 (82.6%) had LVEF >40%. During 1-year follow-up, the primary endpoint occurred in 20.2% of patients with LVEF ≤40% and 17.0% of those with LVEF >40% (adjusted HR 1.28, 95% CI 0.91–1.80; P = .15). Dapagliflozin reduced the risk of the primary endpoint consistently across LVEF subgroups, with no significant interaction between treatment effect and baseline LVEF (P for interaction = .41). Analyses modelling LVEF as a continuous variable confirmed a homogeneous treatment effect across the entire LVEF spectrum. Dapagliflozin was well tolerated, with a safety profile comparable to control across all LVEF categories, although genitourinary infections were more frequent with dapagliflozin. Conclusion In elderly patients undergoing TAVI, dapagliflozin reduced the risk of all-cause death or worsening HF irrespective of baseline LVEF and was safe across the full LVEF spectrum. These findings extend the benefits of SGLT2 inhibition to patients with severe aortic stenosis treated with TAVI, independent of systolic function.